Parental Roles in Developing Children’s Islamic Character in Families: Peran Orang Tua dalam Membentuk Karakter Islam Anak-Anak dalam Keluarga - Farizeni, Yusuf Shabri Amalin; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Families are the first and most influential environment in shaping children’s moral and spiritual development. Specific Background: In the context of Islamic education, parents play a central role as role models, educators, and guides in introducing religious values. Knowledge Gap: Previous studies rarely focus on the practical strategies used by parents in everyday family life to instill Islamic values. Aim: This study aims to describe parental roles and methods in shaping children’s Islamic character within the family setting. Results: Using a qualitative descriptive approach with observation, interviews, and documentation, the findings reveal that parents consistently apply role modeling, habituation, communication, and guidance in character formation. Challenges such as limited time and digital media influence are managed through wise supervision and family involvement. Novelty: The study provides a practical illustration of Islamic parenting practices in a specific community context. Implications: These results highlight the importance of strengthening family-based religious education to nurture morally grounded future generations. Highlights: Parents are key role models in character formation Consistent parenting builds strong Islamic values Communication strengthens emotional and moral bonding Keyword: Parental Role, Islamic Character, Family Education, Moral Development, Qualitative Research